1987
DOI: 10.1093/ajcp/87.5.669
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Fatal Mediterranean Spotted Fever

Abstract: A 77-year-old woman from rural Spain had a febrile summertime disease develop with rash, eschar, and pulmonary, abdominal, and neurologic signs and symptoms. Mediterranean spotted fever (MSF) was diagnosed late in the course, and antirickettsial treatment was given only during the last 30 hours of life. Clinical manifestations of severe disseminated vascular injury included thrombocytopenia, hypoalbuminemia, edema of the lungs and legs, and severe prerenal azotemia. The diagnosis was documented by specific ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 0 publications
1
28
0
3
Order By: Relevance
“…1 Generally, the primary focus involves mainly small sylvan mammals of class Rodentia as hosts for vector arthropods that transmit infections of domestic and synanthropic animals, which may play a role in the maintenance of Rickettsia in nature. 2 Experimental studies with some small rodents have demonstrated that they are susceptible to rickettsial infection and develop rickettsemia at levels high enough to infect their ectoparasites during blood feeding.…”
Section: Introductionmentioning
confidence: 99%
“…1 Generally, the primary focus involves mainly small sylvan mammals of class Rodentia as hosts for vector arthropods that transmit infections of domestic and synanthropic animals, which may play a role in the maintenance of Rickettsia in nature. 2 Experimental studies with some small rodents have demonstrated that they are susceptible to rickettsial infection and develop rickettsemia at levels high enough to infect their ectoparasites during blood feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly because of delays in diagnosis and timely start of doxycycline therapy, however, MSF can result in significant morbidity and mortality. More recently, a severe form of MSF has also been reported, supported by evidence of vascular lesions in kidneys, gastrointestinal tract, liver, spleen, and skin and complications leading to meningoencephalitis, Guillain-Barré syndrome, hypoxemia, multiorgan failure, and death (25,26,28,34,35,46). A clinical study of severe MSF cases in Algeria documented a fatality rate as high as 54.5% among the patients with multiorgan involvement of the disease, despite implementation of treatment with antibiotics (26).…”
mentioning
confidence: 98%
“…Brain lesions consist of a mononuclear leukocyte infiltration of the blood vessel wall and perivascular space [9], but perivascular lymphohistiocytic infiltrates [1] and petechial brain hemorrhage have also been observed. The brain MRI showed that our patient had vasculitic lesions, multiple periventricular white matter lesions without contrast enhancement interpreted as sequelae, and only one contrast-enhanced lesion in the right thalamus suggesting a recent vascular origin and interpreted as an active lesion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean spotted fever, also known in the medical literature as Boutonneuse fever and Marseilles fever [1], is an emerging zoonosis associated with Rickettsia conorii infection, an obligate intracellular, gram-negative bacterium. It is a member of the spotted fever group of rickettsiae and is widely distributed throughout southern Europe, Africa, and the Middle East.…”
Section: Introductionmentioning
confidence: 99%